Enhanced proactive control under stress: divergent neural dynamics of social vs. Monetary rewards in table tennis athletes - Xu, L.; Peng, Z.; Lian, J.; Shao, Y.; Dong, Y.; Fu, W. (Frontiers in Sports and Active Living, 2025)
Background: In high-stress competitive sports, athletes rely on proactive control, a core process that maintains goal-relevant information during anticipated conflicts, which is modulated by motivational rewards. While prior studies have established reward's general benefits on cognitive performance, it remains unclear whether monetary (extrinsic) and social (intrinsic) rewards mitigate stress effects through divergent neurocognitive pathways.